Disaggregated Impact Analysis of Trade on Growth: The Role of Financial Openness in Nigeria - Omo-Ikirodah, Beatrice Onawunreyi (Olsztyn Economic Journal, 2022)
This paper decomposes and estimates the impact of foreign trade on economic growth and evaluates the relevance of financial openness in the relationship in Nigeria using annual time series data between 1987 and 2020. The key findings of the paper are that although trade positively drives economic growth, the effect is due largely to the contribution of the non-oil export component in the long run and short run. This, however, does not rule out the fact that non-oil import over the long run and short run or the overall value of import in the long run lead to a high economic growth in the economy provided higher degree of financial openness is tolerated. In that, subject to broadening the scope of financial openness, Nigeria’s participation in international trade will result in rapid economic growth both in the long run and short run.